2005
DOI: 10.1051/vetres:2005026
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein response and renal failure in canine Babesia annae infection

Abstract: -Babesia annae piroplasms have recently been recognised as a cause of infection and disease among dogs in Europe. The pathogenesis and clinical implications of this emerging disease remain poorly understood. We conducted this study to describe the electrophoretic profiles associated with the infection and to determine if B. annae associated azotaemia is caused by renal failure. We examined by microscopy 2 979 canine blood samples submitted to a diagnostic laboratory in NW Spain between September 2001 and April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 18 publications
(19 reference statements)
4
25
1
5
Order By: Relevance
“…A severe regenerative haemolytic anemia and moderate to severe thrombocytopenia are common findings among dogs infected with the B. microti -like piroplasm [60,61]. In the present report, the three dogs had regenerative anaemia, based on reticulocyte count (performed only for the bitch), presence of polychromasia, anisocytosis and nucleated RBC.…”
Section: Discussionmentioning
confidence: 46%
“…A severe regenerative haemolytic anemia and moderate to severe thrombocytopenia are common findings among dogs infected with the B. microti -like piroplasm [60,61]. In the present report, the three dogs had regenerative anaemia, based on reticulocyte count (performed only for the bitch), presence of polychromasia, anisocytosis and nucleated RBC.…”
Section: Discussionmentioning
confidence: 46%
“…On the other hand, we have observed hypoalbuminemia with lower A/G ratio in infected dogs. Similarly, decreases of albumin have been observed in canine Babesia annae infection (Camacho et al 2005). Low albumin concentra- tion indicates impaired liver functions.…”
Section: Discussionmentioning
confidence: 63%
“…However, no significant correlations were found between serum globulin concentrations and enzyme activities in preeclamptic group. Several investigators have demonstrated the usefulness of serum protein electrophoresis for the initial evaluation of various clinical or pathological conditions in animals (Harrus et al 1996;Altintas et al 2001;Giordano et al 2004;Camacho et al 2005). Numerous studies have focused on mediators associated with the metabolic changes arising in ewe pregnacy toxemia (Marteniuk and Herdt 1988;Scott et al 1995;Harmeyer and Schlumbohm 2006), however, there are no data regarding a serum protein pattern in ewes with pregnancy toxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific diagnosis can rarely be made with serum protein electrophoresis, processes of diseases can be recognized by serum protein patterns and alterations to these patterns are associated with a variety of different conditions and diseases (Ritzman and Daniels 1982). It has been established that the serum protein patterns are changed in viral (Giordano et al 2004), bacterial (Harrus et al 1996) and parasitological (Camacho et al 2005) infections of animals. Several studies have focused on various metabolic alterations arising in the ewe pregnancy toxemia (Cantley et al 1991;Henze et al 1994;Sargison et al 1994;Harmeyer and Schlumbohm 2006).…”
Section: Introductionmentioning
confidence: 99%